2018
DOI: 10.1097/iae.0000000000001774
|View full text |Cite
|
Sign up to set email alerts
|

Value of Fractal Analysis of Optical Coherence Tomography Angiography in Various Stages of Diabetic Retinopathy

Abstract: The optical coherence tomography angiography FD is significantly lower in both superficial and deep capillary plexuses in eyes with all stages studied of diabetic retinopathy. The results were more often significant for the deep capillary plexus. The use of fractal analysis provides an objective criterion to assess microvascular disease burden in diabetic retinopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
3
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 18 publications
4
42
3
2
Order By: Relevance
“…25 In a 2019 study, Hsiao et al 15 concluded that poor visual acuity in diabetic maculopathy was significantly correlated with decreased DCP-VD, and no correlation was found with SCP-VD. Previous studies also reported significant effects on DCP-VD, more than on SCP-VD, in DR patients, and concluded that DCP-VD may be a useful tool for the prediction of DR severity and identifying subjects at high risk, even in the absence of any signs of DR. 23,[33][34][35] These results disagree with other studies, which stated Abbreviations: S, significant; HS, highly significant; FAZ, foveal avascular zone; SCP-VD, superficial capillary plexus vessel density; DCP-VD, deep capillary plexus vessel density; DM, diabetes mellitus; NPDR, non-proliferative diabetic retinopathy; PDR, proliferative diabetic retinopathy. that DR severity and BCVA were significantly correlated with SCP-VD rather than DCP-VD.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…25 In a 2019 study, Hsiao et al 15 concluded that poor visual acuity in diabetic maculopathy was significantly correlated with decreased DCP-VD, and no correlation was found with SCP-VD. Previous studies also reported significant effects on DCP-VD, more than on SCP-VD, in DR patients, and concluded that DCP-VD may be a useful tool for the prediction of DR severity and identifying subjects at high risk, even in the absence of any signs of DR. 23,[33][34][35] These results disagree with other studies, which stated Abbreviations: S, significant; HS, highly significant; FAZ, foveal avascular zone; SCP-VD, superficial capillary plexus vessel density; DCP-VD, deep capillary plexus vessel density; DM, diabetes mellitus; NPDR, non-proliferative diabetic retinopathy; PDR, proliferative diabetic retinopathy. that DR severity and BCVA were significantly correlated with SCP-VD rather than DCP-VD.…”
Section: Discussioncontrasting
confidence: 58%
“…that DR severity and BCVA were significantly correlated with SCP-VD rather than DCP-VD. [27][28][29][30][31][32][33][34][35][36] We found a significant negative correlation between the BCVA (LogMAR) and vessel density in both DCP and SCP. Our results are comparable to a study by Samara et al; 25 however, no correlation was found between them in another study.…”
Section: Discussionmentioning
confidence: 51%
“…[ 60 ] FD has been shown to be an early indicator of DR.[ 77 ] FD is reduced in both SCP and DCP in diabetic patients compared to healthy controls,[ 70 77 ] and the reduction may be more pronounced in DCP. [ 78 ] In contrast, some studies found that FD is increased in PDR cases in both SCP and DCP. [ 72 ] FD was found to be correlated with HbA1c and renal impairment.…”
Section: Resultsmentioning
confidence: 98%
“…This has been measured using a novel variable interscan time analysis (VISTA) algorithm utilized in a non-commercial swept source OCTA. [ 78 ]…”
Section: Resultsmentioning
confidence: 99%
“…The macular nonperfusion area was significantly increased in both superficial and deep vascular layers in patients with NPDR compared to control subjects [14, 22]. Fractal dimension in patients with NPDR was decreased in both retinal vascular layers compared to control subjects [13, 25, 27]. In contrast, another group reported increased fractal dimension in both vascular layers of patients with NPDR compared to control subjects [23].…”
Section: Octa Parameters In the Superficial Deep And/or Intermediatmentioning
confidence: 99%